Reporting on pan-European criteria and indicators for sustainable forest management: Experiences from Liechtenstein 2003 - Aljoscha Requardt; Michael Köhl; Felix Näscher (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2007)
In order to monitor and report progress towards sustainable forest management (SFM), the third Ministerial Conference on the Protection of Forests in Europe (MCPFE) adopted a set of pan-European criteria and indicators in Lisbon in 1998. The criteria and indicators cover economical, ecological and social-cultural aspects of sustainable forest management at the national level. After a revision required by the same conference, an improved set of 35 quantitative pan-European indicators for SFM was adopted at the fourth MCPFE in Vienna in April 2003. The quantitative indicators require certain statistical information, specified by a number of classifications and attributes. This information has to be reported at the national level in order to enable a comprehensive picture of forests and their management within Europe. In 2002-2003, the Principality of Liechtenstein together with the Chair of Biometrics and Forestry Informatics of the Technical University of Dresden conducted a national case study aiming at a comparison between international data demands on one hand and national data availability on the other. In total, almost 200 data attributes were checked and analysed with respect to data availability and data potential. Results show large discrepancies between data demand and data availability. For some indicators the difference between the data required and data availability was enormous. Data were available for only 55% of the required attributes. Reported data and information were partly subject to certain restrictions and did not always completely fulfil the data requirements. The data availability (and also the reasons for no data being available) varied from indicator to indicator, and even from criterion to criterion. Based on the analysed data availability and the documented data report it was also possible to evaluate the available and reported data according to their data source as well as to their temporal and spatial resolution. In doing so, an extensive picture of the current data situation for Liechtenstein (data availability plus data consistency) is presented.
urn:nbn:de:gbv:253-200912-dk039299-3
Keywords: 630; MCPFE; criteria and indicators; sustainable forest management; data requirements; data availability; data potential; reporting